Comparison of perceived stress among medical and engineering students of Karpaga Vinayaga Educational Group, Kancheepuram District, Tamil Nadu - D. C., Vidya; N., Swetha; D., Thirunaaukarasu; H., Gladius Jennifer; E., Karthikeyan (International Journal Of Community Medicine And Public Health, 2017)
Background: Doctors and engineers are experiencing stress from their student life. There are very few studies from South India, which have looked into comparison of perceived stress among medical and engineering students. Hence, this study was attempted with an objective to estimate the overall prevalence and to compare the perceived stress, and to know associated factors influencing stress, among medical and engineering students of Karpaga Vinayaga Educational group, Kancheepuram district, Tamil Nadu. Methods: A cross sectional study was conducted in Karpaga Vinayaga Educational Institute, Tamil Nadu, from June to September 2016. Based on simple random sampling, students from medical and engineering college were selected. After obtaining informed consent, a self administered questionnaire was administered. The data was analysed in SPSS version 18.0. Results: Out of 560 study subjects, 135 (24.2%) had low stress, 390 (69.6%) had moderate stress and 35 (6.2%) severe stress. Stress was associated with personal problems OR=2.29 (95% CI: 1.19-4.39), sleep disturbance OR=4.12 (95% CI: 1.57–10.7), difficulty in understanding the subject OR=2.32 (95% CI: 1.19–4.53), difficulty in time management OR=2.47 (95% CI: 1.40–4.35) and home sickness (p=0.001) in medical students whereas among engineering students, stress was associated with personal problems OR=2.01 (95% CI: 1.02–3.92), sleep disturbance OR=2.14 (95% CI: 1.1–4.1) and difficulty in time management OR=2.6 (95% CI: 1.48–4.58). Conclusions: The overall prevalence of perceived stress was 75.8%. The prevalence of perceived stress among medical students was 76.8% as compared to 75% of engineering students. Among medical and engineering students, stress was associated with personal problems, sleep disturbance and difficulty in time management.